Prediction of Neurological Outcome in High Risk Neonates: Prospective Study - Pikala Tarakeswara Rao; Manem Saisunil Kishore; Gundapaneni Manasa; Chokkakula Sanyasi Naidu (JCDR Research and Publications Pvt. Ltd., 2018)
Introduction: High risk babies are vulnerable to neurological brain injury. Early identification of injury will help in initiating strategies to reduce the neurological damage and hence prevent long term sequeale. It's also help in counselling the parents regarding the prognosis. Neurosonography and Doppler are point of care tests commonly used to identify neurological damage. Aim: To identify spectrum of neurological abnormalities in high risk neonates. Second objective is to know the predictive ablility of initial findings of neurosonogram and Doppler findings on neurological outcome. Materials and Methods: This is a prospective study conducted in neonatal care unit of tertiary hospital. Total of 138 neonates admitted to hospital are enrolled in the study. All neonates underwent transcranial USG using standard probe and Resistive Index (RI) measured in right anterior and right Middle Cerebral Artery (MCA) with color Doppler equipment within 72 hours of life. Babies upon discharge followed up in neonatal clinic and neurological assessment done at six months of age. Analysis was done using statistical software packages SPSS and Microsoft Excel. Results: Diffuse cerebral ooedema was detected by neurosonogram in 20 (19.2%) of high risk neonates. RI index less than 0.6 was observed in 32 (30.8%) Anterior Cerebral Artery (ACA) and 47 (45.3%) MCA. Statistically significant neonates with initial abnormal USG findings had abnormal outcome at six months of age compared to neonates with normal USG findings (p=0.014). Low RI in the middle and ACA was associated with abnormal outcome at six months in significant number of neonates (p<0.001). RI of right MCA is more specific in predicting neurological outcome at six months of age. The positive likelihood ratio is more for low RI of MCA (18) as compared to neurosonogram. Conclusion: Abnormal neurological outcome was significantly more in neonates with abnormal findings on USG and Doppler. Doppler RI abnormalities done within 72 hours had more specificity and better likelihood ratio for predicting abnormal neurological outcome than neurosonogram.